Dietary patterns and birth outcomes of healthy Lebanese pregnant women - Papazian, Tatiana; Salameh, Pascale; Abi Tayeh, Georges; Kesrouani, Assaad; Aoun, Carla; Abou Diwan, Mia; Rabbaa Khabbaz, Lydia (Frontiers in Nutrition, 2022)
Background: The aim of this study was to define the dietary patterns (DPs) of a sample of Lebanese pregnant women and to establish their correlation with maternal and neonatal outcomes. Methods: A cross-sectional study was conducted among 358 Lebanese pregnant women. Maternal socio-demographic variables, anthropometric measurements, gestational weight gain and neonatal outcomes such as weight, length, head circumference and Apgar score were collected by qualified dietitians. Dietary intake was assessed by a validated food frequency questionnaire and three 24-hour dietary recalls. DPs were determined, a posteriori, by a factor analysis to distinguish the inter-correlations between the food groups and a cluster analysis method to assemble the participants into groupings based on similarities in food consumption. Results: The identified DPs were not exclusively composed of specific food groups, since some components were overlapping in the DPs. The first one was characterized by a high consumption of starchy vegetables, unsaturated fats and unhealthy foods, the second was rich in fruits and vegetables, seeds, rice and pasta, and in fried local meals and the third was mainly based on protein-rich foods like poultry, fish, eggs and dairy products. They were named respectively as "Westernized", "Mixed" and "Neo-Mediterranean" by the research team. Women having the lowest pre-gestational body mass index (BMI) and higher gestational age followed mainly the "Neo-Mediterranean" eating pattern. Conclusion: The three identified DPs among Lebanese pregnant women were correlated with the pre-gestational BMI, and some maternal variables. However, neither the maternal nor the neonatal outcomes were correlated with the DP adopted by the mothers. Keywords: Dietary patterns; Pregnancy; Neonatal outcomes; Body Mass Index; Gestational weight gain.